2014
DOI: 10.1016/j.clay.2014.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic wet peroxide oxidation of 4-chlorophenol over Al-Fe-, Al-Cu-, and Al-Fe-Cu-pillared clays: Sensitivity, kinetics and mechanism

Abstract: Al-Fe-, Al-Cu-, and Al-Fe-Cu-PILCs were synthesized, characterized and tested in the catalytic wet peroxide oxidation of 4-chlorophenol (4-CP). An apparent induction period followed by a rapid oxidation was observed during the Fenton-like reaction, and the whole reaction could be modeled well using a Fermi's kinetic equation (R 2 = 0.9938~0.9993). The generation of hydroxyl radicals (HO • ) from surface-catalyzed decomposition of H 2 O 2 was the oxidation cause whereas the dissolution of active metals was its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Thus, heterogeneous metal-oxide catalysts, such as CuO (Kim and Ihm 2007;Hua, Ma, and Zhang 2013), TiO 2 (Cervantes et al 2013;Pintar, Batista, and Tišler 2008), Graphene oxide , and ZrO 2 (Wei et al 2013) have recently been used. Of these catalysts, CuO is highly active in the decomposition of phenolic compounds, including phenol (Ayusheev et al 2014; A c c e p t e d M a n u s c r i p t 4 Domínguez et al 2014;Lefèvre et al 2011;Wang et al 2014;Yan, Jiang, and Zhang 2014;Yang et al 2014), dye (Ovejero et al 2013;Fu and Kyzas 2014) and chlorophenol (Wei et al 2013a;Zhou et al 2014;Lee, Lin, and Jou 2012). We previously found that 10 wt% CuO/AlR 2 ROR 3 R could catalyze the wet oxidation of aniline making possible high degradation to COR 2 R at temperatures ranging from 160 to 230°C under air pressure ranging from 5 to 10 bars for two hours (Sriprom et al 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Thus, heterogeneous metal-oxide catalysts, such as CuO (Kim and Ihm 2007;Hua, Ma, and Zhang 2013), TiO 2 (Cervantes et al 2013;Pintar, Batista, and Tišler 2008), Graphene oxide , and ZrO 2 (Wei et al 2013) have recently been used. Of these catalysts, CuO is highly active in the decomposition of phenolic compounds, including phenol (Ayusheev et al 2014; A c c e p t e d M a n u s c r i p t 4 Domínguez et al 2014;Lefèvre et al 2011;Wang et al 2014;Yan, Jiang, and Zhang 2014;Yang et al 2014), dye (Ovejero et al 2013;Fu and Kyzas 2014) and chlorophenol (Wei et al 2013a;Zhou et al 2014;Lee, Lin, and Jou 2012). We previously found that 10 wt% CuO/AlR 2 ROR 3 R could catalyze the wet oxidation of aniline making possible high degradation to COR 2 R at temperatures ranging from 160 to 230°C under air pressure ranging from 5 to 10 bars for two hours (Sriprom et al 2014).…”
Section: Introductionmentioning
confidence: 97%
“…8,119 PILCs catalysts have been reported by Galeano et al 3 to achieve high rates of pollutants removal with a very high stability and a minimal leaching of the interlayered metal species. 7,118,120 Garrido-Ramírez et al 120 and Zhou et al 7 reported that PILCs can also perform over a wide range of pH and temperature and can be readily separated from the aqueous solution and retain their catalytic activity in repeated cycles. They reported relatively short operation times owing to the high catalytic activity of the PILCs.…”
Section: Advanced Oxidation Processesmentioning
confidence: 99%
“…Nevertheless, modication of natural clay minerals by pillaring using suitable pillaring agents has emerged as a promising technique because it allows for opening of the clay layers, producing high resistance and thermal stability, increased porosity, surface area and basal spacing as well as other physicochemical characteristics. 7,8 The pillaring method is based on a mechanism of cationic exchange in which robust inorganic molecules are introduced in the interlayer space of the clay minerals forming oxides strongly bound to layers of the minerals. 9 The hydroxyl polycations of polynuclear metals, such as Al, Fe, Zr, Cr and Ti, are types of inorganic pillaring agents that have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption is an economical method for water decontamination applications and for separation in analytical purposes, and it is frequently used for the removal of phenolic pollutants [12]. Different adsorbents such as activated carbon [13,14], zeolites [15], clay [16,17] and chitosan [18,19] were investigated for the removal of phenol and phenolic pollutants from wastewater. Even if activated carbon, obtained from different carbonaceous materials such as wood, nutshells and fruit stones, peat, charcoal, lignite, bituminous coal, and petroleum coke, are the most widely used adsorbents, the relatively high cost, the poor mechanical strength and sorbent losses during regeneration, limit their use [20].…”
Section: Introductionmentioning
confidence: 99%